Dermal capillary rarefaction as a marker of microvascular damage in patients with rheumatoid arthritis: Association with inflammation and disorders of the macrocirculation. (31st May 2018) - Anyfanti, Panagiota; Gkaliagkousi, Eugenia; Triantafyllou, Areti; Zabulis, Xenophon; Dolgyras, Panagiotis; Galanopoulou, Vasiliki; Aslanidis, Spyros; Douma, Stella
Abstract: Objective: Capillary rarefaction is observed in various cardiovascular diseases, yet it remains understudied in RA, a chronic inflammatory disease accompanied by excess cardiovascular risk. We quantified capillary density in RA patients and explored potential associations with macrocirculatory disorders, inflammation, and cardiovascular risk. Methods: Dermal capillary density was assessed with nailfold capillaroscopy in RA and non‐RA individuals, using specifically designed semiautomated software. Macrocirculation assessments included large artery stiffening, evaluated with PWV, and myocardial blood flow, calculated as cardiac index from impedance cardiography. Cardiovascular risk score was estimated from the Framingham Heart Study. Results: The number of capillaries per visual field was lower in patients (n = 99) compared to controls (n = 35) (132.6 ± 30.3 vs 152.9 ± 25.2, P  = .001). In the RA group, capillary density negatively correlated with CRP and PWV, and positively with HDL and cardiac index. In the multivariate analysis, CRP independently predicted capillary rarefaction ( P  = .044). Capillary density significantly correlated with cardiovascular risk, even after adjustment for inflammation ( P  = .030). Conclusion: Capillary rarefaction appears pronounced in RA and correlates with lower cardiac output, increased arterial stiffness, and cardiovascular risk. However, the associations with macrocirculatory disorders may be obscured by inflammation, which appears as the major contributor to capillary rarefaction in RA.